Gerakan Sekolah Cantik Tanpa Lipstik: Menanamkan Pendidikan Karakter Muslimah di Lingkungan SMAN 1 Pacet - Ravina Anggie Esna Putri; Aisyah Jihan Nurkhafiza; Tazkiyatur Rizqillah Fauzi; Saifuddin Zuhri (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
The development of popular culture and social media has created new beauty standards among teenagers, especially female students, who tend to emphasize physical appearance aspects such as the use of cosmetics as a symbol of self-confidence. This phenomenon also occurs in the environment of SMAN 1 Pacet, where some female students show a dependence on lipstick and facial makeup in school activities, thus potentially shifting the values of modesty, shame (haya'), and morals from an Islamic perspective. This study aims to describe and analyze the implementation of the